(untitled) (Symposium on Natural and Applied Sciences, 2026)
In the conditions of modern economy, the level of socio-economic development of the regions is largely determined by investment flows. Investment, in turn, is directly related to the quality and level of the investment climate formed in a particular area. Investment climate is the complex combination of economic, legal, political, institutional and infrastructural conditions for investors that is the main factor determining the effectiveness of capital investments. In this regard, the assessment of the investment climate in the context of regions and its impact on investment attractiveness is a scientifically and practically relevant issue. In the current era of increasing global economic integration, competition between countries to attract investment is becoming increasingly intense. Reducing regional development imbalances by improving the investment climate is an important strategic task, especially for developing countries, including Uzbekistan. By assessing the investment climate by regions, it is possible to create new jobs, increase export potential, and reduce interregional economic gaps.